2020
DOI: 10.1021/jacs.0c04357
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Multiplex H-Bonds

Abstract: H-bonding is the predominant geometrical determinant of biomolecular structure and interactions. As such, considerable analyses have been undertaken to study its detailed energetics. The focus, however, has been mostly reserved for H-bonds comprising a single donor and a single acceptor. Herein, we measure the prevalence and energetics of multiplex H-bonds that are formed between three or more groups. We show that 92% of all transmembrane helices have at least one non-canonical H-bond formed by a serine or thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 52 publications
3
19
0
Order By: Relevance
“…PSiUr3 and PSiUr4 show two peaks of the amino group within 3500 to 3300 cm −1 , that is due to the crystallization effect which is further clarified by X‐rays data (XRD) in Figure 3f. [ 43,44,45 ] It can be seen in Figure 3f that the crystallization degree of all PSiUr samples is very different. The crystallization is mainly caused by the conjugation of the benzene ring on the diaminodiphenyl disulfide.…”
Section: Resultsmentioning
confidence: 99%
“…PSiUr3 and PSiUr4 show two peaks of the amino group within 3500 to 3300 cm −1 , that is due to the crystallization effect which is further clarified by X‐rays data (XRD) in Figure 3f. [ 43,44,45 ] It can be seen in Figure 3f that the crystallization degree of all PSiUr samples is very different. The crystallization is mainly caused by the conjugation of the benzene ring on the diaminodiphenyl disulfide.…”
Section: Resultsmentioning
confidence: 99%
“…However, here a bare cholesterol molecule is docked to a bare protein molecule surrounded by two bare bilayer interfaces, all in a hydrophobic environment, so that docking energies will include hydrogen bonding between cholesterol and protein and between cholesterol and the interfacial region of the lipid bilayer. It has been suggested that a multiplex hydrogen bond in which a single hydrogen bond acceptor interacts with multiple hydrogen bond donors is ca 60% stronger than a single, canonical hydrogen bond (Feldblum and Arkin 2014 ; Brielle and Arkin 2020 ) and the hydrogen bond detector in Chimera (Pettersen et al 2004 ) suggests that multiplex hydrogen bonds are formed between a cholesterol –OH and the bilayer interface. Concentrations of cholesterol in a membrane are best expressed in mole fraction units and the standard free energy for formation of a canonical hydrogen bond in a hydrophobic environment in mole fraction units is – 6.5 kcals mol −1 (Ben-Tal et al 1997 ; Feldblum and Arkin 2014 ) giving an energy for a multiplex hydrogen bond between cholesterol and the bilayer interface of ca – 10.4 kcals mol −1 ; this was the value used to interpret binding energies for cholesterol with GABA A receptors (Lee 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…[29] Root-mean-square fluctuations (RMSF) measurements were performed for protein Cα atoms. Hydrogen bonds analysis between ACE2 and S1-RBD was performed at a cut-off distance of 3.5 Å and a cut-off A-D-H angle of 20° using the “Hydrogen Bonds” analysis extension in VMD [31, 32]. Interfacial residues were determined from the available ACE2-S1-RBD complex (PDB ID: 6m0j) at a cut-off distance of 5 Å using PyMOL.…”
Section: Methodsmentioning
confidence: 99%